Efficacy of Toluidine Blue Staining in Rectal Biopsy with Patients of Hirschsprung Disease (KYAMC Journal, 2023)
Background: The diagnosis of Hirschsprung disease (HD) is dependent on the histological study of rectal biopsy for ganglion cells and nerve fibers. Hematoxylin and Eosin (H&E) stain is commonly used. However, diagnosis is not possible with H&E staining every time, because staining has limitations in the diagnosis of immature ganglion cells in neonates and in the submucosal area where the ganglion cells are small in number. Using Toluidine blue (Tb) stain it has become easier to identify ganglion cells.Objective: To find out the efficacy of toluidine blue staining in the diagnosis of Hirschsprung disease.Materials and Methods: A cross-sectional descriptive observational study was carried out with the histological findings of 60 rectal punch biopsies and 60 full-thickness rectal biopsies from the corresponding same patients from March 2018 to February 2020. Ten cases of inadequate punch biopsy were excluded from the study. After paraffin embedding, slides were stained with H&E and Tb stains. Then stained sections were examined for the presence or absence of ganglion cells and hypertrophic nerve fibers in the submucosa and in between muscle layers. Result: Out of 50 punch biopsy cases, 33(66.0%) cases with H&E stain and 35(70.0%) cases with Tb stain showed presence of hypertrophic nerves (HN). In Non-HD cases, with H&E stain 11(22.0%) cases showed somewhat easy to identify ganglion cells. By using Tb stain ganglion cells were easy to identify in 4(8.0%) cases and somewhat easy to identify in 8(16.0%) cases. Out of 60 full-thickness rectal biopsy 38(63.30%) cases showed presence of hypertrophic nerves in both H&E and Tb stains. In Non-HD cases with H&E stain ganglion cells somewhat easy to identify in 8(13.3%) cases; easy to identify in 9(15.0%) cases and very easy to identify in 2(3.3%) cases. By using Tb stain, the identification of ganglion cells were 1(1.7%), 9(15.0%) and 9(15.0%) respectively. Study showed Tb stain was superior to H&E in the identification of ganglion cells and hypertrophic nerves.Conclusion: Toluidine blue stains should be used as the routine stain in adjunct to H&E stain to highlight ganglion cells in suspected Hirschsprung disease.KYAMC Journal Vol. 14, No. 02, July 2023: 69-73.